Adaptations in upper-body maximal strength and power output resulting from long-term resistance training in experienced strength-power athletes - Baker, D. G.; Newton, R. U. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this investigation was to observe changes in maximal upper-body strength and power and shifts in the load-power curve across a multiyear period in experienced resistance trainers. Twelve professional rugby league players who regularly performed combined maximal strength and power training were observed across a 4-year period with test data reported every 2 years (years 1998, 2000, and 2002). Upper-body strength was assessed by the 1 repetition maximum bench press and maximum power during bench press throws (BT Pmax) with various barbell resistances of 40-80 kg. During the initial testing, players also were identified as elite (n = 6) or subelite (n = 6), depending upon whether they participated in the elite first-division national league or second-division league. This subgrouping allowed for a comparison of the scope of changes dependent upon initial strength and training experience. The subelite group was significantly younger, less strong, and less powerful than the elite group, but no other difference existed in height or body mass in 1998. Across the 4-year period, significant increases in strength occurred for the group as a whole and larger increases were observed for the subelite than the elite group, verifying the limited scope that exists for strength gain in more experienced, elite resistance-trained athletes. A similar trend occurred for changes in BT Pmax. This long-term observation confirms that the rate of progress in strength and power development diminishes with increased strength levels and resistance training experience. Furthermore, it also indicates that strength and power can still be increased despite a high volume of concurrent resistance and endurance training.